PENGARUH TAX AVOIDANCE DAN CORPORATE GOVERNANCE TERHADAP COST OF DEBT - Pambudi setyo cahyono; Kartika Hendra Titisari; Endang Masitoh (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The purpose of this study is to examine the effect of tax avoidance and corporate governance on cost of debt where corporate governance is proxied as managerial ownership, institutional ownership, independent commissioners, and audit quality. In analyzing data, This study uses multiple linear regression analysis method and sampling method is purposive sampling. Sample of this study is 33 manufacturing companies listed on the BEI in 2016-2018 who have published financial reports for 3 years which comes from the official site Bursa Efek Indonesia. The results showed that tax avoidance and corporate governance have an effect on the cost of debt, partially independent commissioner has an effect on cost of debt while managerial ownership, institutional ownership and audit quality have no effect. Keywords : Tax avoidance, corporate governance, cost of debt Abstrak Tujuan penelitian ini menguji pengaruh tax avoidance dan corporate governance terhadap cost of debt dimana corporate governance diproksikan sebagai kepemilikan manajerial, kepemilikan institusional, komisaris independen, dan kualitas audit. Dalam menganalisis data, penelitian ini menggunakan metode analisis regresi linear berganda dan pengambilan sampel menggunakan metode purposive sampling. Sampel penelitian 33 perusahaan manufaktur yang terdaftar di BEI tahun 2016-2018 yang telah menerbitkan laporan keuangan 3 tahun yang berasal dari situs resmi Bursa Efek Indonesia. Hasil penelitian menunjukkan bahwa tax avoidance dan corporate governance berpengaruh terhadap cost of debt , secara parsial komisaris independen berpengaruh terhadap cost of debt sedangkan kepemilikan manajerial, kepemilikan institusional, dan kualitas audit tidak berpengaruh. Kata Kunci: Tax avoidance, corporate governance, cost of debt